PEMBELAJARAN CERITA PENDEK DENGAN MODEL PROJECT BASED LEARNING BERBANTUAN FOTOGRAFI PADA SISWA KELAS XI SMA NEGERI 1 JAWAI - Atikah, Nur; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Universitas Tanjungpura, 2024)
Learning short stories requires imaginative skills that can be supported by a good and an immersive educational approach includes the Project Based Learning framework assisted by photography. This research aims to determine crafting narratives through the Project Based Learning methodology assisted by photography in students in the 11th grade at SMA Negeri 1 Jawai. The research methodology employed is Classroom Action Research (CAR). The data source of this research is students in the 11th grade IA2 at SMA Negeri 1 Jawai and the data are students' project reports. The findings of the study indicate that students short story writing skills with the PBL learning model experienced improvement. The improvement in students' short story writing skills from pre-action to cycle 1 was 16%, from an average pre-action score of 62.77 to 72.77 in cycle 1, and From the first phase to the second phase, there was a 12% increase, with the average score improving from 72.77 in phase 1 to 81.33 in phase 2. Students' short story writing skills improved by 30% overall, with the average score increasing from 62.77 before the intervention to 81.33 afterward, aligning with the learning objectives to achieve mastery.